An efficient approximate analytical technique for the fractional model describing the solid tumor invasion - Chethan, H. B.; Saadeh, Rania; Prakasha, D. G.; Qazza, Ahmad; Malagi, Naveen S.; Nagaraja, M.; Sarwe, Deepak Umrao (Frontiers in Physics, 2024)
In this manuscript, we derive and examine the analytical solution for the solid tumor invasion model of fractional order. The main aim of this work is to formulate a solid tumor invasion model using the Caputo fractional operator. Here, the model involves a system of four equations, which are solved using an approximate analytical method. We used the fixed-point theorem to describe the uniqueness and existence of the model’s system of solutions and graphs to explain the results we achieved using this approach. The technique used in this manuscript is more efficient for studying the behavior of this model, and the results are accurate and converge swiftly. The current study reveals that the investigated model is time-dependent, which can be explored using the fractional-order calculus concept.